If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x = -5x + 6 Reorder the terms: -6x = 6 + -5x Solving -6x = 6 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -6x + 5x = 6 + -5x + 5x Combine like terms: -6x + 5x = -1x -1x = 6 + -5x + 5x Combine like terms: -5x + 5x = 0 -1x = 6 + 0 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6
| 7h-8m=4-2m | | X+9x-2+5x-1=23 | | 17v/2=34(2) | | 7y+6-(y+2)= | | 8.4=36+1.2z | | w/8=12.5 | | 4x+8=16+5x | | 14/35/7/10 | | 8(x-6)=-4(x+6)-12 | | 11=3-4f | | 1=95+7h | | 7(x-6)=63 | | B-4b=36 | | 0.5(6x-3)=(1+x) | | x+.7=-.3 | | -3[9+5]=12 | | -2x-5=-8x+25 | | 6x+3=8z-5 | | 7m-8m=12-4m | | 7.4x-15.5=51.1 | | X+3=-1-3x | | 4r(-4r+5)= | | 3x+40=310 | | X^3-11x^2-9x+155=0 | | x+.7=.3 | | 4p+(-2p)=15-4 | | X^4-4x^2-140=0 | | (a+6)(a^2-6a+5)= | | 21+x=45 | | -18x-19=-55 | | 4(x-50)+x=180 | | 2w+2+2= |